(untitled) (Journal of International Studies, 2014)
Key Issues of Mongolia’s “Third Neighbour” Policy: Concept, History and Contemporary Case This article talks about Mongolia’s “third neighbor” policy such is origins of “third neighbour” term, purpose and nature of "third neighbor" policy, implementation mechanism, key issues in contemporary, challenges and idea in Mongolian diplomatic history of XX century.